Behold-- the dragons! - Gibbons, Gail. (New York : Morrow Junior Books, 1999)
Explains how myths about dragons developed, different types of dragons, what draconologists do, and how different cultures portray dragons.
School Library Journal
Booklist
Teacher Librarian
6.4
K-3
Keywords: Dragons -- Juvenile literature; Dragons; Folklore; Dragons; Folklore